Indexing temporal RDF graph - Yan, Li; Zhao, Ping; Ma, Zongmin (Computing, 2019)
Time data can be found in various real-world applications and different models have been proposed to model temporal information. With the wide utilization of the Web and the availability of massive Web resources, temporal Resource Description Framework (RDF) model has attracted more and more attention. In this paper, we propose an index approach for temporal RDF graphs to effectively query massive temporal RDF data. We build the prefix path index for querying subjects of temporal RDF triples and the suffix index for querying objects of temporal RDF triples, respectively. Meanwhile, we use frequent elements to improve the efficiency of the index we proposed. We also adopt B-tree index to manage all elements of triples. Our index approach can support inserting and deleting temporal triples in temporal RDF graphs. Experimental results show that our index approach can efficiently process queries in temporal RDF graphs.